Photocatalytic ozonation of model aqueous solutions of oxalic and oxamic acids
Degradation of aqueous solutions of oxalic acid (OXA) and oxamic acid COMA), the final oxidation products of several organic compounds, has been investigated by photocatalytic ozonation. The combined method was carried out comparing P25 to synthesized sol-gel TiO2, and composites of TiO2 and multi-walled carbon nanotubes (MWCNTs) obtained either by the sal-gel method or by the hydration-dehydration technique. Photo-ozonation in the presence of P25 resulted in total conversion of OXA after 15 min. Concerning OMA, P25 and composites containing 80 and 90% wt of P25 led to complete degradation more rapidly. The reaction rate constants, k(app,) were 15 x 10(-2) min(-1) for P25,8.8 x 10(-2) min(-1) and 8.2 x 10(-2) min(-1) for the composite with 80 and 90% wt of P25, respectively. OMA removal by photocatalytic ozonadon is here reported for the first time and a remarkable conversion is obtained with complete degradation achieved in a short period of time in the presence of TiO2, P25 and composites with 80 and 90%wt of P25 and MWCNTs and with 80%wt of P25 and oxidized MWCNTs. By performing single photocatalysis or single ozonation for selected materials, a synergetic effect of the combined method was identified.